2015
DOI: 10.1038/srep15394
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Iridium(III) Complexes Supported by N-Heterocyclic Carbene-based C^C^C-Pincer Ligands and Aromatic Diimines

Abstract: Iridium(III) hydrido complexes containing N-heterocyclic carbene (NHC)-based pincer ligand 1,3-bis(1-butylimidazolin-2-ylidene)phenyl anion (C1^C^C1) or 1,3-bis(3-butylbenzimidazolin-2-ylidene)phenyl anion (C2^C^C2) and aromatic diimine (2,2′-bipyridine (bpy), 1,10-phenanthroline (phen), 4,4′-dimethyl-2,2′-bipyridine (Me2bpy), or dipyrido-[3,2-f:2′,3′-h]-quinoxaline (dpq)) in the form of [Ir(C^C^C)(N^N)(H)]+ have been prepared. Crystal structures for these complexes show that the Ir–CNHC distances are 2.043(5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“… 44 However, [3 + 2 + 1] iridium complexes containing tridentate ligands which bear bis(NHC) ligands are yet to be investigated. Wong et al reported a class of [3 + 2 + 1] iridium complexes 45 containing tridentate bis(NHC) ligands, wherein bipyridine served as the bidentate ligand and hydride as the monodentate ligand. As a result, these complexes are inherently salts, leading a hurdle in utilization through evaporated process into fabrication as PhOLEDs.…”
Section: Introductionmentioning
confidence: 99%
“… 44 However, [3 + 2 + 1] iridium complexes containing tridentate ligands which bear bis(NHC) ligands are yet to be investigated. Wong et al reported a class of [3 + 2 + 1] iridium complexes 45 containing tridentate bis(NHC) ligands, wherein bipyridine served as the bidentate ligand and hydride as the monodentate ligand. As a result, these complexes are inherently salts, leading a hurdle in utilization through evaporated process into fabrication as PhOLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…This class of dianionic chelates is distinctive from tridentate chelates such as 1,3-bis­(benzimidazol-2-yl)­benzene, bis­(imidazol-2-ylidene) benzene, and tridentate polypyridyl chelate, employed by the research groups of Haga, De Cola, and Bernhard, from which higher emission efficiency was also recorded for the isolated Ir­(III) complexes. Moreover, the monoanionic ancillary chelate can be the bidentate or tridentate heteroaromatic cyclometalate with either terminal pyridyl-based donor(s) (i.e., chelates L (2) and L (3) ) or imidazolylidene appendage(s) (i.e., chelates L (4) , L (5) , and L (6) ). Since the C-donor of imidazolylidene and analogues is known to exert relatively stronger metal–ligand bonding (or ligand field strength) than that of the N-based donor such as pyridine, the imidazolylidene-coordinated Ir­(III) emitters would exhibit better emission efficiency than those possessing only the N-donor. This strategy is especially crucial to the blue emitters with higher emission energy. One recent report is the syntheses of bis-tridentate Ir­(III) phosphors bearing both 2-phenyl-6-(pyrazol-3-yl) pyridine class of chelate L (1) and di-imidazolylidene pincer of ancillary L (6) , and fabrication of the true-blue phosphorescent OLEDs using the same .…”
Section: Introductionmentioning
confidence: 99%
“…340 nm (ε < 9.1 × 10 3 M −1 cm −1 ) are mainly assigned as the triplet metal-to-ligand and intraligand charge transfer ( 3 MLCT and 3 ILCT) transitions. 55 S49 in the Supporting Information). It has been well reported that emitters with a short lifetime will help alleviate the triplet−triplet annihilation), which is known as the triplet excitons' relaxation process and is the principal reason of the efficiency roll-off.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Apart from these, the [3 + 2 + 1]-coordinated iridium­(III) complexes with one tridentate, bidentate, and monodentate ligand have been increasingly reported recently. Such versatile molecular design may offer an alternative pathway to fine-tune the photophysical and electrochemical properties of the emitters. Figure b illustrates the schematic structures of iridium­(III) complexes in [2 + 2 + 2], [3 + 3], or [3 + 2 + 1] coordination modes. ,,, Upon varying the bidentate ligand from substituted arylpyridine to NHC ligands, the emission energy of the [3 + 2 + 1]-coordinated iridium­(III) complexes could be effectively tuned to cover the whole visible region, ranging from 386 to 609 nm.…”
Section: Introductionmentioning
confidence: 99%